Rethinking the role of context in mathematics education - Patronis, Tasos (NOMAD Nordic Studies in Mathematics Education, 1997)
In this paper the role of context in teaching and learning mathematics is considered from a «local» and then from a «global» point of view. The «local» viewpoint focuses on context as a «scene» providing meaning to the mathematical content, while the «global» one addresses the problem of transformation of a given context, which arises when the teacher intends to put the students into a new perspective of mathematical knowledge. Both these viewpoints are used in an attempt to relate context to the metonymic transformation of the meaning of words used in mathematics. From this point of view various mathematical and empirical (classroom) examples are discussed and reinterpreted in the paper.